Prosodic and Paralinguistic Features of Multiple English Varieties and the Attitudes and Performance of Korean Learners of English - Pollard, Andrew (Curtin University, 2020)
This convergent mixed methods study explores prosodic and paralinguistic features of nine English speaker origins pertinent to Korean learners of English and how language attitude formation and English listening comprehension may be affected. The study found prosodic features (tone, clarity, rhythm, pausing, filled pausing) and paralinguistic features (talking to oneself, crying) interact with language attitude formation and English listening comprehension, which has implications for practice, pedagogy and policy in Korea and the wider ELF context.